EFECTOS DE LA EROSIÓN SIMULADA Y MANEJO DE RESIDUOS SOBRE LA PRODUCTIVIDAD DE UN ALFISOL DEL ESTADO GUÁRICO, BAJO CULTIVO DE SORGO (Sorghum bicolor) - Lobo, Deyanira; Vivas, Rigoberto (Venesuelos, 2011)
Palabras claves: Abstract Soil erosion is a main land degradation process. This process has been widely studied, but not the erosion-productivity relationships. The purpose of this study was to evaluate the effects of simulated erosion and residues management on water, soil and nutrient losses, and soil productivity, using sorghum (Sorghum bicolor) as an index crop. The experiment was carried out under greenhouse conditions on a Typic Haplustalf, from Chaguaramas, Guárico State, Venezuela. The treatments included 0, 50 and 100% removal of the surface horizon, and 0, 2 and 5 Kg/ha of residues (Cenchrus ciliaris) left on the soil surface, in a completely randomized experimental design, with three replications. The experimental units were erosion boxes (20 cm x 30 cm and 10 cm depth) each with five plants of sorghum, which were harvested after 40 days. Simulated rainfall (33 mm, at 70 mm/h) was applied every 8 days. Soil, water and nutrients losses, plant height, dry matter production, and root depth were evaluated. The increment of remotion levels of the surface horizon increased runoff and soil erosion, and reduced plant height and rooting depth. The differences between remotion levels of the surface horizon were highly significant. The increment in levels of residue cover resulted reduced runoff and soil loss, and increased plant height and root depth. Key words: Erosion, vegetables residues, productivity, sorghum Abstract Soil erosion is a main land degradation process. This process has been widely studied, but not the erosion-productivity relationships. The purpose of this study was to evaluate the effects of simulated erosion and residues management on water, soil and nutrient losses, and soil productivity, using sorghum (Sorghum bicolor) as an index crop. The experiment was carried out under greenhouse conditions on a Typic Haplustalf, from Chaguaramas, Guárico State, Venezuela. The treatments included 0, 50 and 100% removal of the surface horizon, and 0, 2 and 5 Kg/ha of residues (Cenchrus ciliaris) left on the soil surface, in a completely randomized experimental design, with three replications. The experimental units were erosion boxes (20 cm x 30 cm and 10 cm depth) each with five plants of sorghum, which were harvested after 40 days. Simulated rainfall (33 mm, at 70 mm/h) was applied every 8 days. Soil, water and nutrients losses, plant height, dry matter production, and root depth were evaluated. The increment of remotion levels of the surface horizon increased runoff and soil erosion, and reduced plant height and rooting depth. The differences between remotion levels of the surface horizon were highly significant. The increment in levels of residue cover resulted reduced runoff and soil loss, and increased plant height and root depth. <span style="font-family: "Arial","sans-serif"; font-size: 10pt; mso-fareast-font-family: SimSun; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-font-weight: bold; mso-bidi-language: AR-SA;" lang="EN-US">Key words: Erosion, vegetables residues, productivity, sorghum Erosión, residuos vegetales, productividad, sorgo